Decision Science: A New Hope. Issue 6 (December 2019) - Curley, Lee J.; MacLean, Rory; Murray, Jennifer; Laybourn, Phyllis
Decision science is an area of enquiry that crosses many disciplines, from psychology to economics, each with their own perspective of decision-making. Traditionally, mathematicians have envisaged decision-making as a purely rational endeavor, whereas psychologists and behavioral economists have critiqued this narrative and suggested that cognitive short cuts are the real mechanisms behind how decisions are made. However, contemporary dual process theorists argue that two systems of the mind exist: system 1 (intuitive decision-making) and system 2 (rational decision-making). The current review will present a relatively new metaphor for decision-making: the unified threshold model. This model is a global approach to decision-making which allows both intuitive and rational decision-making processes to be explained in a more flexible manner than the dual process model. This review will introduce the reader to different types of threshold models (counter and diffusion), their assumptions, and their ability to explain decision-making behavior. Implications and future research will also be discussed. In summary, the aim of this review is to highlight that a rather than the unified threshold model of decision-making may give a more adequate explanation of decision-making data in comparison to previous models and theories.